A Remote Assay for Measuring Canine Platelet Activation and the Inhibitory Effects of Antiplatelet Agents. (2nd December 2017) - Dunning, M.; May, J.; Adamany, J.; Heptinstall, S.; Fox, S.
Abstract : Background: Antiplatelet medications are increasingly used in dogs. Remote analysis of platelet activity is challenging, limiting assessment of antiplatelet drug efficacy. Hypothesis/Objectives: To evaluate a method used in humans for stimulation and remote analysis of canine platelet activity. Animals: Forty‐five dogs of various ages without a coagulopathy or thrombocytopenia. Six were receiving antiplatelet medication. Methods: Prospective observational study. Platelets were stimulated with combinations of arachidonic acid (AA) and epinephrine (Epi) or adenosine diphosphate (ADP) and the thromboxane A2 ‐mimetic U46619 (U4). PAMFix was added to the blood samples to facilitate delayed analysis of platelet activity. Activity was assessed by flow cytometric measurement of surface P‐selectin (CD62P) expression. Results: Canine platelets could be stimulated with both AA/Epi and ADP/U4. The levels of P‐selectin were significantly greater than paired, unstimulated samples ( P  < 0.001). Inhibition of P‐selectin expression occurred after this stimulation by adding antiplatelet drugs in vitro. The efficacy of antiplatelet drugs in samples from treated dogs was also measurable ex vivo using this method. Delayed analysis of platelet activity at time points up to 22 days demonstrated excellent correlation between respective mf values at each time point (r 2  = 0.92, P  < 0.0001). Conclusions and Clinical Importance: This study evaluated a new method to remotely assess canine platelet activity. It shows that PAMFix can be used for this purpose. This provides opportunities to interrogate the inhibitory action of antiplatelet drugs in clinical settings.